2018
DOI: 10.4328/jcam.5414
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of procalcitonin, C-reactive protein, and erythrocyte sedimentation rate for acute complicated appendicitis

Abstract: Aim: Acute appendicitis (AA) is one of the most common surgical emergencies. Despite extraordinary advances in modern investigations, an accurate diagnosis of AA remains an enigmatic challenge. The purpose of this study was to examine the laboratory parameters studied during the preoperative period in patients who were histopathologically diagnosed with AA; C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and procalcitonin (PCT) in the differential diagnosis of complicated/uncomplicated appendic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Synthesis of AFP proteins occurs in the liver as a result of cytokines released from tissue macrophages, and these proteins reflect nonspecifically the presence and severity of inflammation. [26,27] Proteins whose synthesis increase due to AFY are called positive reactants, while those whose synthesis decrease is termed acute phase reactants. In acute phase response secondary to inflammation in the organism, the amount of CRP increases, whereas the amount of albumin decreases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of AFP proteins occurs in the liver as a result of cytokines released from tissue macrophages, and these proteins reflect nonspecifically the presence and severity of inflammation. [26,27] Proteins whose synthesis increase due to AFY are called positive reactants, while those whose synthesis decrease is termed acute phase reactants. In acute phase response secondary to inflammation in the organism, the amount of CRP increases, whereas the amount of albumin decreases.…”
Section: Discussionmentioning
confidence: 99%
“…[28] CRP is an acute phase reactant used quite frequently in the diagnosis of AA, and its sensitivity ranges from 40.0 to 95.6%, and its specificity varies from 53 to 82%. [27] In many studies examining the relationship between AA and CRP, the CRP level was reported to be especially high in complex appendicitis cases, such as perforation and periapical abscess. [27,29] Using a CRP cut-off level of 20 mg/L, Ayrık et al [14] reported a sensitivity level of 54.33% and a specificity level of 56.06% for CRP in AA cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels reflect the severity of acute appendicitis. Very high levels may reveal more complicated cases or sepsis [24]. WBC and neutrophil ratio, CRP, procalcitonine and SER are the most often used markers.…”
Section: What's the Role Of Inflammatory Markers In Diagnosis And Gramentioning
confidence: 99%